2002
DOI: 10.1007/s00438-002-0757-3
|View full text |Cite
|
Sign up to set email alerts
|

The product of Saccharomyces cerevisiae WHIP/MGS1, a gene related to replication factor C genes, interacts functionally with DNA polymerase δ

Abstract: The Saccharomyces cerevisiae gene WHIP/ MGS1 encodes a protein related to the subunits of Replication Factor C (RFC). We found that the RFC-like motifs in Whip/Mgs1 are essential for its function. Furthermore, by screening for synthetic dosage lethality, we have shown that overexpression of MGS1 causes lethality in combination with mutations in genes that encode replication proteins such as DNA polymerase delta, RFC, PCNA and RPA. Moreover, loss of MGS1 function interferes with the ability of multicopy PCNA to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(81 citation statements)
references
References 49 publications
(61 reference statements)
3
77
0
1
Order By: Relevance
“…When PCNA is polyubiquitinated in this manner, it promotes damage bypass through template-switching (Zhang and Lawrence, 2005;Torres-Ramos et al, 2002;Blastyak et al, 2007). Interestingly, deletion of RAD18 or MMS2 suppresses the growth defect of Polδ mutants, and a similar phenomenon was observed after deleting MGS1 (Branzei et al, 2002b). Moreover, mgs1 mutation suppresses the growth defect of a Polδ mutant caused by expression of E. coli RuvC, a bacterial Holliday junction resolvase, suggesting that Mgs1 generates a Holliday junction-like structure that may be formed in the process of the template-switch type of damage bypass (Hishida et al, 2002).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…When PCNA is polyubiquitinated in this manner, it promotes damage bypass through template-switching (Zhang and Lawrence, 2005;Torres-Ramos et al, 2002;Blastyak et al, 2007). Interestingly, deletion of RAD18 or MMS2 suppresses the growth defect of Polδ mutants, and a similar phenomenon was observed after deleting MGS1 (Branzei et al, 2002b). Moreover, mgs1 mutation suppresses the growth defect of a Polδ mutant caused by expression of E. coli RuvC, a bacterial Holliday junction resolvase, suggesting that Mgs1 generates a Holliday junction-like structure that may be formed in the process of the template-switch type of damage bypass (Hishida et al, 2002).…”
Section: Introductionmentioning
confidence: 83%
“…On the other hand, genetic evidences obtained from analyses of budding yeast mutants indicate that Mgs1 may function in a DNA damage tolerance pathway that is similar to, but distinct from, the pathway involving Rad6, Rad18, Rad5, Mms2, and Ubc13, and has been postulated to be a template-switch type of damage avoidance pathway (Hishida et al, 2002;Branzei et al, 2002bBranzei et al, , 2004. Very recently, biochemical evidences supporting a Rad18-and Rad5-driven template-switch at stalled forks was reported (Branzei et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…nation intermediates. Previous studies of Mgs1 suggested that its function is somehow related to the function of DNA polymerase δ (Polδ), which is required for cellular DNA replication (Hishida et al, 2002;Branzei et al, 2002b). In this context, we have observed stimulation of Polδ activity by WRNIP1 at the initiation stage in vitro (Tsurimoto et al, 2005).…”
mentioning
confidence: 55%
“…12) In addition, overproduction of Mgs1p is lethal or very toxic when it is combined with mutations in the genes that encode proteins involved in DNA replication, such as replication protein A, replication factor C, proliferating cell nuclear antigen and DNA polymerase d (Pold). 13) Mgs1p physically and functionally interacts in vivo with budding yeast Pol31, the second subunit of Pold. 14) Human WRNIP1 also interacts directly with human Pold and stimulates the DNA synthesizing activity of Pold by increasing initiation frequency of DNA synthesis from primers annealed on template DNA (template-primer DNA).…”
mentioning
confidence: 99%